Ají de ratón (Capsicum annum) en agua de bebida como promotor de crecimiento en pollos de engorde - Córdova Gómez, Pablo Joel (2025)
The present study aimed to evaluate the effect of mouse chili pepper extract (Capsicum annuum) in drinking water as a growth promoter in Cobb 500 broiler chickens. 180 chickens were used, distributed in three treatments with six repetitions: T0 (control, without chili), T1 (0.12% chili pepper in water) and T2 (0.22% chili pepper in water). Variables such as weight gain, feed conversion, feed intake, viability, mortality, gastrointestinal pH and cost-benefit ratio were analyzed. The results show that the addition of chili pepper significantly improved weight gain (p <0.05), where T2 obtained the greatest increase with 2.84 Kg, also the feed conversion was significantly more efficient in the groups with the addition of chili extract obtaining T2: 1.70 and T1: 1.74 Kg/Kg, without affecting feed intake. Viability and mortality did not present statistical differences (p>0.05), indicating that mouse chili does not compromise bird health. Furthermore, a significant increase (p<0.05) in crop and proventriculus pH was recorded in treatments with chili addition. However, the cost-benefit ratio was favorable for T0, due to the increased cost of the extract. In conclusion, the addition of 0.22% mouse chili extract to drinking water improves growth and feed efficiency in broiler chickens, without negative effects on their health, proving an alternative for maintaining metabolism and good digestion.